1998
DOI: 10.1002/(sici)1096-9861(19980222)391:4<444::aid-cne3>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel receptor protein tyrosine phosphatase (RPTP?) and acidic fibroblast growth factor (FGF-1) transcripts delineate a rostrocaudal boundary in the granule cell layer of the murine cerebellar cortex

Abstract: We have identified a novel receptor-like protein tyrosine phosphatase (RPTPrho) transcript whose expression in the cerebellar cortex is restricted to the granule cell layer of lobules 1-6. Acidic fibroblast growth factor (FGF-1) mRNA follows a similar cerebellar expression pattern. Together, the two markers define a sharp boundary in lobule 6, slightly caudal to the primary fissure. Anterior and posterior compartments became discernible only during postnatal weeks two and six, for RPTPrho and FGF-1, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 73 publications
(62 reference statements)
1
22
0
Order By: Relevance
“…2 c-f and i). Expression of Fgf-1, an anterior granule compartment marker (15), and Igfbpl1, an additional growth factor pathway component, were not altered (SI Fig. 21 c-f), indicating that the decrease in Igfbp5 was specific and not due to a general expression deficiency of all anterior compartment genes or growth factors.…”
Section: Resultsmentioning
confidence: 97%
“…2 c-f and i). Expression of Fgf-1, an anterior granule compartment marker (15), and Igfbpl1, an additional growth factor pathway component, were not altered (SI Fig. 21 c-f), indicating that the decrease in Igfbp5 was specific and not due to a general expression deficiency of all anterior compartment genes or growth factors.…”
Section: Resultsmentioning
confidence: 97%
“…RPTPρ is the most recently isolated member of the IIB family [6, 7]. Northern blot and in situ hybridization studies have shown that RPTPρ is largely restricted to the central nervous system [6].…”
Section: Introductionmentioning
confidence: 99%
“…Northern blot and in situ hybridization studies have shown that RPTPρ is largely restricted to the central nervous system [6]. Within the CNS, expression is developmentally regulated and, in the mouse, delineates a unique boundary region in the granule cell layer of the cerebellar cortex [7]. Motifs in the RPTPρ extracellular segment (MAM, Ig and FN-III domains) are commonly found in cell adhesion molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have described the genomic structure of human PTPρ [8] and have shown that the transcript is expressed primarily in the central nervous system where it delineates a distinct developmental compartment in the cerebellar cortex [9,10]. In the present study, the genomic structures of all four murine R2B genes (PTPκ, PTPμ, PTPρ and PCP-2) were compared, and their expression localized to specific cell types within the central nervous system.…”
Section: Introductionmentioning
confidence: 91%